Problem solving and structured programming with Pascal - Behforooz, Ali; Holoien, Martin O. (California : Brooks/Cole Publishing Company, 1986)
Our aim in writing this books is to help teach students the skills and concepts needed to become good problem solvers capable of using the Pascal language well.
Chapter 1. Problem solving and algorithm development -- Chapter 2. Introductory programming concepts -- Chapter 3. Introductory control concepts and structures -- Chapter 4. Program errors -- Chapter 5. Introduction to functions and procedures -- Chapter 6. More on type and variable declarations -- Chapter 7. More on control structures -- Chapter 8. More on functions and procedures plus recursion -- Chapter 9. More on structured data types -- Chapter 10. Introduction to data structures.
Includes bibliographical references and index.
Keywords: PASCAL (COMPUTER PROGRAM LANGUAGE)